2018
DOI: 10.4103/ijn.ijn_240_16
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of cyclosporine versus tacrolimus in steroid and cyclophosphamide resistant nephrotic syndrome: A prospective study

Abstract: Calcineurin inhibitors (CNIs) are the preferred drugs for treatment of childhood steroid-resistant nephrotic syndrome (SRNS) who are also resistant to cyclophosphamide (CYC). Although few studies have shown a benefit of one over the other, efficacy and safety of either CNIs (tacrolimus [TAC] or cyclosporine [CSA]) in this special population remained to be assessed in long-term studies. Forty-five children with SRNS who were also resistant to CYC (CYC-SRNS) from January 2006 to June 2011, were included in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Several studies have shown the effectiveness of PDN in relapsing SRNS at 2 mg/kg/day to induce remission [52,53] with a change to QOD PDN, followed by tapering until the end of month 6 [185,186]. Intravenous MPDN was also effective in inducing remission in relapsing patients [71,74,187].…”
Section: Evidence and Rationalementioning
confidence: 99%
“…Several studies have shown the effectiveness of PDN in relapsing SRNS at 2 mg/kg/day to induce remission [52,53] with a change to QOD PDN, followed by tapering until the end of month 6 [185,186]. Intravenous MPDN was also effective in inducing remission in relapsing patients [71,74,187].…”
Section: Evidence and Rationalementioning
confidence: 99%
“…While other CNIs like voclosporin are currently being tested in clinical trials, CSA and TAC are the two major agents which are commonly used in the treatment of nephrotic syndrome. TAC and CSA are generally accepted to have similar therapeutic effects [ 7 ], showing similarly superior efficacy over CPM [ 29 ] and no significant difference in the numbers of SRNS patients achieving remission [ 30 , 33 ]. Prasad et al studied 45 children with SRNS who were resistant to CPM, in which they treated the patients with either CSA or TAC and compared treatment outcome at 6 months [ 33 ].…”
Section: Intensified Immunosuppression and Adjuvant Agents For Srnsmentioning
confidence: 99%
“…TAC and CSA are generally accepted to have similar therapeutic effects [ 7 ], showing similarly superior efficacy over CPM [ 29 ] and no significant difference in the numbers of SRNS patients achieving remission [ 30 , 33 ]. Prasad et al studied 45 children with SRNS who were resistant to CPM, in which they treated the patients with either CSA or TAC and compared treatment outcome at 6 months [ 33 ]. They showed that CNIs were effective in CPM-resistant nephrotic syndrome and reported comparable results of TAC and CSA in inducing remission in 70% and 82% of patients, respectively ( P = 0.3) [ 33 ].…”
Section: Intensified Immunosuppression and Adjuvant Agents For Srnsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, tacrolimus is a more potent immunosuppressant than cyclosporin 15 with a more favorable renal safety profile. [16][17][18] It also compares favorably with cyclophosphamide for inducing remission in steroiddependent/steroid-resistant adults with MCNS, [19][20][21] and is effective as rescue therapy for patients who have failed treatment with other immunosuppressants. [21][22][23] In addition to its immunosuppressive action, tacrolimus acts directly on podocytes 24,25 to stabilize the actin cytoskeleton and reduce levels of angiopoietin-like protein 4, a protein associated with podocyte injury and the pathogenesis of proteinuria in MCNS.…”
mentioning
confidence: 99%